circ_JMJD1C expedites breast cancer progression by regulating miR-182-5p/JMJD1C/SOX4 axis: The roles of circ_JMJD1C in breast cancer - Xu, Renyuan; Lan, Haomiao; Zhang, Li; Yang, Sisi; Mao, Yu; Che, Hongying (Cellular and Molecular Biology, 2024)
Circular RNAs (circRNAs) are engaged in various types of cancers. This study aimed to investigate the roles of circ_0006743 (circ_JMJD1C) in breast cancer. The downstream of circ_JMJD1C and their interaction network was determined by bioinformatic analyses. Gene expression were analyzed through western blot and qRT-PCR assays. Functional assays were conducted in vitro and in vivo to verify circ_JMJD1C role in BC. FISH and confocal analysis indicated the cellular distribution of circ_JMJD1C. Luciferase reporter, RNA immune-precipitation (RIP) assays, as well as Pearson’s correlation analysis, were implemented to test the relation of miR‐182-5p, JMJD1C and circ_JMJD1C. Circ_JMJD1C and JMJD1C expression were both elevated, and their expression was positively correlated in BC. Circ_ JMJD1C knockdown hindered BC cell proliferation, invasion, and migration, along with epithelial-mesenchymal transition (EMT) in vitro and in vivo. Circ_JMJD1C facilitated BC progression by the miR‐182-5p-JMJD1C axis. Circ_JMJD1C epigenetically upregulated SOX4. Circ_JMJD1C promotes the aggressiveness of BC via regulating miR‐182-5p/JMJD1C/SOX4 axis. This may provide a novel and promising therapy targeting BC.